1999
DOI: 10.4315/0362-028x-62.11.1270
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Microflora of Wild Brown Trout (Salmo trutta), Wild Pike (Esox lucius), and Aquacultured Rainbow Trout (Oncorhynchus mykiss)

Abstract: Initial numbers of bacteria associated with wild (brown trout and pike) and cultured (rainbow trout) freshwater fish as well as with the water in which they were caught were determined. Subsequently, a total of 979 randomly selected isolates were characterized and identified to the genus level. For all counts performed (aerobes, psychrotrophs, anaerobes, Enterobacteriaceae, and enterococci), no significant differences were observed in water samples, the highest level corresponding to psychrotrophs in pike envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
59
5
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 21 publications
7
59
5
3
Order By: Relevance
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…[36]. These values obtained in this study are close to the values reported earlier for aquacultured fresh trout from Spain [37,41], Greece [38,39] and U.K [40]. It is widely accepted that the initial microbial load of fresh water varies depending on water conditions and temperature.…”
Section: Resultssupporting
confidence: 78%
“…Raw trout is a fish with a fat content of 1.60 ± 0.12 g/100 g edible meat, a protein content of 19.80 ± 0.65 g/100g edible meat and ash content of 0.61±0.23 g/100g edible meat. The levels of fat and ash were low compared to that reported for trout from other regions [58][59][60]41]. During storage in ice, no significant variations in the composition of major constituents viz.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The gastrointestinal microflora of fish appears to be simpler than that of endotherms and predominant bacterial genera/species isolated from most fish guts have been aerobes or facultative anaerobes (Ringo et al 1995(Ringo et al , 2001). However, a few recent studies have reported a wider diversity of the gut microflora than believed previously (Ringo et al 2006;Hovda et al 2007;Ward et al 2009), especially in the intestinal contents of freshwater fish (Gonzalez et al 1999;Spanggaard et al 2000;Wu et al 2010;Cantas et al 2012). In contrast to what is reported for seawater fish, the intestinal microflora of freshwater fish species tends to be dominated by members of the genera Aeromonas, Plesiomonas, representatives of the family Enterobacteriaceae, and obligate anaerobic bacteria (Hansen and Olafsen 1999).…”
Section: Introductionmentioning
confidence: 52%
“…There have been some reports on the incidence of A. hydrophila in Switzerland, in Taiwan, in Malaysia, in Italy, in India, in China; and P. shigelloides in Japan, USA, in Czech Republic, in Spain, in Greece (Arai ., 1980;Tsai & Chen, 1996;Bardon, 1999;Gonzalez, Lopez-Diaz, Prieto, & Otero 1999;Radu, Ahmad, Ling, & Reezal 2003;Ottaviani et al, 2006;Papadopoulou et al, 2007;Nagar, Shashidhar, & Bandekar 2011;Shao-wu, Di, Hong-bai, & Tong-yan 2013). In Turkey the incidence of these pathogens in seafood products have not been extensively investigated.…”
Section: Introductionmentioning
confidence: 99%